Influence of variety, harvesting date and drying temperature on the composition and the in vitro digestibility of corn grain. (January 2018) - Odjo, Sylvanus; Béra, François; Beckers, Yves; Foucart, Guy; Malumba, Paul
Abstract: This study aimed at assessing the influence of corn variety, harvesting date and drying temperature on the composition and the in vitro digestion of dry matter, starch and crude protein of mature corn grain. Two corn grains varieties harvested at two different dates after physiological maturity (at two different moisture contents) were analyzed for their composition and dried in a fluidized-bed dryer between 54 and 130 °C. The corn varieties differed in their chemical composition while the harvesting date had only a significant impact (p < 0.05) on the neutral detergent fibre content. The dried samples were then submitted to a sequential in vitro pepsin-pancreatin digestion. Crude protein digestibility is influenced by corn variety and decreases when drying temperature and moisture content increase. The in vitro digestibilities of dry matter and starch increase in the same trend even if they are differently affected by the drying temperature according to the moisture content level. At higher moisture content, the increase in the in vitro digestibility of dry matter and starch follow a linear trend (R 2 > 0.97). It appears that the drying temperature, the harvesting date and the corn varieties may significantly affect the digestion of corn grain major components with possible implication on animal performance. Highlights: Digestibilities of starch and protein aren't affected in the similar way by drying. Higher drying temperatures increase the final digestibility of starch. Crude protein digestibility decreases when drying temperature increases. The effect of drying temperature depends on the initial moisture content of grain.